Extraction of Phosphate from Polluted Waters Using Calcium Alginate Beads Doped with Active Carbon Derived from A. aspera Plant as Adsorbent - Ravulapalli Sujitha; Kunta Ravindhranath (Journal of Analytical Methods in Chemistry)
An adsorbent prepared by entrapping active carbon derived from the stems of Achyranthes aspera plant in the calcium alginate beads (CABAA) has been investigated for its adsorption nature towards the removal of phosphate by varying various physicochemical parameters. Surface morphological studies are made using FTIR, XRD, FESEM, and EDX. The sorption mechanism is analyzed using Freundlich, Langmuir, Dubinin-Radushkevich, and Temkin adsorption isotherms. The adsorption kinetics is found to follow the pseudo-second-order model. Thermodynamic parameters are analyzed and found that the adsorption is endothermic and nonspontaneous in nature. The maximum amount of phosphate adsorbed onto CABAA is found to be 133.3 mg/g of active carbon and, furthermore, the adsorbent is highly selective. The methodology developed is successfully applied to polluted water samples.